Enterovirus Neutralizing Antibodies, Monocyte Toll Like Receptors Expression and Interleukin Profiles Are Similar Between Non-affected and Affected Siblings From Long-Term Discordant Type 1 Diabetes Multiplex-Sib Families: The Importance of HLA Background - Bergamin, Carla Sanchez; Pérez-Hurtado, Elizabeth; Oliveira, Luanda; Gabbay, Monica; Piveta, Valdecira; Bittencourt, Célia; Russo, Denise; Carmona, Rita de Cássia; Sato, Maria; Dib, Sergio A. (Frontiers in Endocrinology, 2020)
Enteroviruses are main candidates among environmental agents in the development of type 1 diabetes (T1D). However, the relationship between virus and the immune system response during T1D pathogenesis is heterogeneous. This is an interesting paradigm and the search for answers would help to highlight the role of viral infection in the etiology of T1D. The current data is a cross-sectional study of affected and non-affected siblings from T1D multiplex-sib families to analyze associations among T1D, genetic, islet autoantibodies and markers of innate immunity. We evaluated the prevalence of anti-virus antibodies (Coxsackie B and Echo) and its relationships with human leukocyte antigen (HLA) class II alleles, TLR expression (monocytes), serum cytokine profile and islet β cell autoantibodies in 51 individuals (40 T1D and 11 non-affected siblings) from 20 T1D multiplex-sib families and 54 healthy control subjects. The viral antibody profiles were similar among all groups, except for antibodies against CVB2, wich were more prevalent in the non-affected siblings. TLR4 expression was higher in the T1D multiplex-sib family’s members than in the control subjects. TLR4 expression showed a positive correlation with CBV2 antibody prevalence (rS: 0.45; P=0.03), CXCL8 (rS: 0.65, P=0.002) and TNF-α (rS: 0.5, P=0.01) serum levels in both groups of T1D multiplex-sib family. Furthermore, within these families, there was a positive correlation between HLA class II alleles associated with high risk for T1D and insulinoma-associated protein 2 autoantibody (IA-2A) positivity (odds ratio: 38.8; P=0.021). However, the HLA protective haplotypes against T1D prevalence was higher in the non-affected than the affected siblings. This study shows that although the prevalence of viral infection is similar among healthy individuals and members from the T1D multiplex-sib families, the innate immune response is higher in the affected and in the non-affected siblings from these families than in the healthy controls. However, autoimmunity against β-islet cells and an absence of protective HLA alleles were only observed in the T1D multiplex-sib members with clinical disease, supporting the importance of the genetic background in the development of T1D and heterogeneity of the interaction between environmental factors and disease pathogenesis despite the high genetic diversity of the Brazilian population.